The formation of B-lymphocyte colonies in agar contained in glass capillaries. - Ulmer, A (1978)
Optimal conditions were established for a micro method for the production of colonies of B lymphocytes from mouse spleen cells cultured in agar in glass capillaries, in the presence of bacterial lipopolysaccharide (LPS). Besides LPS the cultures require 5 X 10(-5) M mercaptoethanol and 20% horse serum for optimal colony growth. Foetal calf serum and heat-inactivated horse or foetal calf serum were found to be inferior. An agar gel strength of 0.3% was best for colony counting. A sigmoid curve was obtained when the number of colonies formed was related to the seeded cell density suggesting that some kind of cell to cell co-operation is essential for colony formation. The daily kinetics of colony growth were followed by microscopic colony counting and photometric capillary scanning with integration of the signal areas. Both methods indicated that colony growth had ceased by day 6. The combination of both methods gave the most realistic picture of B-lymphocyte colony development.